Pengaruh Penggunaan Media Audio Visual terhadap Kualitas dan Kemantapan Gerak Jurus Tunggal IPSI - Firah, Maghfirah Salsabila Putri; Hamdani, Hamdani; Hartoto, Setiyo; Prakoso, Bayu Budi (Physical Education Departement of University PGRI Jombang, 2024)
This study aims to identify and measure the effect of using audiovisual media on the quality and stability of IPSI single moves. The weak experimental method was used with a one-group pretest-posttest design protocol. 17 extracurricular pencak silat students were involved in 8 meetings using audiovisuals in learning IPSI single moves. A total of 4 IPSI standard certified assessors assessed students during the pre and post-test using IPSI standard instruments. Descriptive statistical analysis, normality, and t-tests were done using SPSS version 25 software. The results showed that the quality of movement seemed to increase as indicated by a significant decrease in the number of errors (t = 3.96, p = 0.001) but the movement stability did not change (t = 1.00, p = 0.332). This finding explains that audiovisual media is suitable for improving the quality of movement but not the stability of movement. Therefore, in the future, trainers need to find other media to provide appropriate training in improving the stability of movement. In addition, the volume of training needs to be considered in providing an impact on movement stability according to various other relevant sources.